An examination of risk profiles among justice-involved girls: do race and place matter? - Krupa, Julie M. (Deviant behavior, 2022)
Studies addressing risk factors among justice-involved girls in rural areas remain a neglected area of research. Following an intersectional framework, the current study examines the patterning of a broad range of risk factors and health needs, across urban and rural contexts, among arrested African American, Hispanic, and white females who participated in a public health service. Results from a latent class analysis suggest significant differences in substance use, physical health, depression, and trauma experiences among the racial/ethnic groups and across geographic setting. This study has implications for prevention, screening and assessment procedures of arrested youths, and intervention services in the juvenile justice system.